Integrating web usability and web aesthetic in public universities websites: A model verification - Affandy, Habee Bullah; Hussain, Azham; Mohd Nadzir, Maslinda (Science and Engineering Research Support Society, 2020)
The role of a website is becoming vital in supporting the daily function of a public university. Public university websites are now becoming more like a hub that offers various services for various categories of users. With the different type of users, it posed a new challenge for web designers, especially in term of integrating the web usability and aesthetics to ensure it is suitable for all users. Both usability and aesthetics have its own importance in the overall web performance thus requires a proper integration mechanism. In order to ensure that there is a guideline for web designers to assist them in designing a proper website, a model was developed that functions as a guideline in assisting web designers to design a public university website that not only high in term of usability but at the same time pleasing in term of aesthetics. In this paper, it discussed the verification process and the results of the verification of the model that was developed. The model was verified through experts in the field of web usability, web aesthetics and web design to ensure the model comply to the requirements of HCI and web design practice.